Mapping teacher status and career-long professional learning: the Place Model. Issue 1 (2nd January 2018) - Clarke, Linda
ABSTRACT: This paper engages with key contemporary debates about teaching and teacher education through proposing an innovative, interdisciplinary model, the Place Model, which uses two senses of 'place' to provide comparative lenses for a timely, a-priori examination of the place of the teacher: place in the humanistic geography tradition as a process – a cumulative, career-long professional learning journey – and, also, place in the sociological sense of teacher status. This article considers a range of international literature before speculatively 'populating' the model with a range of examples in a way which raises important questions about conceptions of teachers across the globe, and provides an alternative and original vision of the profession.